Winter Wheat Response to Different Fungicide Management (Products and Timing of Application) During the 2019-2020 Growing Season - G. Cruppe; B. R. Jaenisch; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
Foliar fungicides can improve wheat grain yield in Kansas, but there is limited information on the efficacy of different products as well as the timing of application. We conducted a field study in five Kansas locations to evaluate the yield, test weight, and protein responses of WB-Grainfield to different commercial fungicides applied at different times during the growing season. The trial was conducted in a randomized complete block design to evaluate (1) a non-treated control; Topguard applied at 5 ounces per acre at (2) jointing, (3) heading, and (4) jointing plus heading; (5) Delaro applied at 6 oz/a at jointing; (6) Absolute Maxx applied at 5 ounces per acre at heading; (7) Delaro at jointing plus Absolute Maxx at heading at the rates previously specified; and (8) Nexicor applied at 13 oz/a at heading. The study was conducted near Conway Springs, Great Bend, two sites near Hutchinson (optimum- and late-sowing date), and Leoti. Grain yield across locations ranged from 36 to 72.9 bushels per acre. A significant fungicide by location interaction on grain yield resulted from two locations showing no response to fungicide; two locations resulting in the highest yield when fungicide at heading was presented in the evaluated treatment; and one location showing all fungicide treatments outyielding the control. Similar results were obtained for test weight, where fungicides at heading seemed to benefit test weight at all locations except at the driest one. There were no consistent effects of foliar fungicide management on wheat grain protein concentration. This research is an initial step in determining the benefits of foliar fungicide to winter wheat yield and to date, a preliminary conclusion highlights the usefulness of a heading fungicide application when precipitation is not a limiting factor to yields, without consistent differences among the evaluated products.
Keywords: wheat; fungicide; variety